Introduction to a special issue on eating disorders and related symptomatology in male populations. Issue 12 (14th October 2019) - Murray, Stuart B.; Griffiths, Scott; Lavender, Jason M.
Abstract: Objective: It is our sincere pleasure to introduce a special issue of the International Journal of Eating Disorders focused on eating disorders and related symptoms in male populations. Method: Contributions focused on three main themes among male populations: (a) the nature of eating disorder symptoms and recovery; (b) long‐term outcomes following eating disorders treatment; and (c) muscularity‐oriented symptoms of eating pathology. Results: The contributions to this special issue highlight the importance of better understanding how eating disorder symptoms manifest, may be maintained, and respond to treatment among male populations. Findings across the articles demonstrate some similarities between male and female samples with respect to core eating disorder symptoms, as well as important differences, particularly with respect to muscularity‐oriented disordered eating. Findings related to treatment outcome also highlight the suboptimal long‐term remission rates and elevated mortality among male inpatients with eating disorders. Discussion: The diverse range of samples, methodologies, and research questions addressed within this collection of papers demonstrates the breadth of the important scientific work on this topic. As eating disorders and related symptoms in male populations continue to be underrecognized and underserved, we hope that this special issue will encourage further high‐quality clinical research in this area.